Resource allocation in health care processes: A case study - Antti Kauhanen; Martti Kulvik; Silja Kulvik; Sirpa Maijanen; Olli Martikainen; Paula Ranta (The Research Institute of the Finnish Economy (ETLA), 2013)
This paper utilizes queuing models to analyze health care processes. We extend previous queuing models to allow for i) heterogeneous resources, ii) resource allocation to various tasks, and iii) teams (complementary resources). We model a process of one clinical unit. We use the model to analyze how resource allocation affects both process performance and utilization of resources. This approach emphasizes how allocation of resources to tasks affects process performance. We illustrate how the model can be used to analyze how variations in resources affect process performance and for example how ICT affects process performance.
Keywords: I12; C61; D24; 330; processes; queues; performance; information and communication technology